Personality determinants of alcoholism - Aranowska, Elżebieta; Brustman, Artur (Studia Psychologica: Theoria et praxis, 2004)
In this paper theoretical models of an alcohol problem formation are discussed using a developmental approach. Authors also refer to many own studies. A source of inspiration to the research were Zücker’s and Tarter’s assumptions, which suggest that factors specific for the alcohol abuse begin to act in an early childhood already, although the usage of alcohol starts much later. In the own research (n = 148) a relationship between the alcohol usage intensity (an own criterion) and personality traits of a college youth was analyzed. Subjects were divided into two groups of attendants to “better” and “worse” schools. The results show that there is an association of the alcohol abuse intensity with psychopathy (reaching the upper limit of a norm - 58th ten), psychasthenia and schizophrenia. The outcomes of the study confirm Zücker’s thesis, concerning antisocial personality of young people, who abuse alcohol. In the “worse” schools as much as 7% of subjects can be treated as at risk of alcoholism (whereas in “better” schools – only 1%).